The study of customer satisfaction on Wisma Embun Sdn Bhd services among the tenants of Wisma Abrar International / Saadatul Hayati Mohamed - Mohamed, Saadatul Hayati (2000)
Creating customer satisfaction through effective and efficient services is one way to build everlasting relationship with customers. Nowadays to maximize satisfaction on services towards customer is a difficult task. Each department of the company must think customer to maintain customer loyalty. The success or failure of the company can be measured through the level of the customer satisfaction. This research is to study the level of customer satisfaction towards the Wisma Embun Sdn Bhd services among the tenants of Wisma Abrar International. To complete this research, the researcher use exploratory studies. Exploratory studies are conducted to clarify and define the nature of the problem. Researcher uses two approaches to collect data. The first approach is by using primary data. There are direct observations, personal interview and lastly distributing questionnaires. Researcher also uses secondary data to get information such as magazines, books and Internet sources. The sample frame in this research is focused only on tenants of Wisma Abrar International Kota Bharu Kelantan. The total respondents involves in this research are 60 respondents. Researcher analyzes data by using SPSS (Statistical Programme Software System) version 8.